Effectiveness of biochar and microbes on the dynamics of available phosphorus in NaCl-stressed soil - Maya Dwi Setyoningrum; Rossyda Priyardhasini; Fitri Wijayanti (Fakultas Pertanian Universitas Yudharta Pasuruan, 2026)
Introduction: Saline soils are characterized by high concentrations of soluble salts and alkaline pH, which limit nutrient availability, particularly phosphorus (P), and reduce soil productivity. This study aimed to evaluate the effectiveness of biochar and microbial inoculants in improving soil chemical properties and P availability under NaCl-induced salinity stress. Methods: The experiment was conducted from December 2024 to March 2025 in a greenhouse using a completely randomized factorial design with two factors: microbial inoculation (control. Pseudomonas sp. and Azotobacter) and biochar types (control, coconut shell, rice husk, mangrove wood and cassava stem) at a rate of 30 tons/ha. Treatments were replicated three times, resulting in 45 experimental units. Soil samples were incubated for 12 weeks with observations every two weeks and analysed for pH, electrical conductivity (EC), available P, and exchangeable Na. Results: The results showed that biochar and microbial inoculants significantly influenced soil pH, EC, and nutrient dynamics. Biochar application reduced EC through ion adsorption and improved soil porosity, while also enhancing P availability via mineral ash contribution and cation exchange processes. Microbial inoculation, particularly Azotobacter, increased P availability through the production of organic acids and phosphatase enzymes, and its effect was more pronounced when combined with biochar. The highest available P was consistently observed in the combination of Azotobacter or Pseudomonas sp and cassava stem biochar. Furthermore, both amendments reduced exchangeable Na, thereby improving soil structure and nutrient balance. Conclusion: In conclusion, the synergistic application of biochar and microbes effectively ameliorates saline soils, enhances phosphorus availability, and represents a sustainable strategy for soil fertility improvement under salinity stress.